2011
DOI: 10.1115/1.4002676
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Toughness of Composite Joints With Carbon Nanotube Reinforcement

Abstract: Fracture toughness tests were conducted for carbon composite scarf joints with and without carbon nanotube (CNT) reinforcement in order to study the effect of CNT on enhancing the fracture toughness of the scarf joint interface. Both mode I (i.e., opening mode) and mode II (i.e., shear mode) fracture tests were undertaken with and without CNT applied locally at the joint interface. During the study, the image correlation technique was used to examine the fracture mechanisms altered by the introduction of CNT. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Previous studies showed that calculation of energy release rates was very useful for predicting the interface joint strength of composites with known critical energy release rates (Kwon et al, 2008a, b;Faulkner and Kwon, 2011;Faulkner et al, 2009; Step/butted joint and step overlap joint Interface fracture of hybrid joint McGuire and Harris, 1974;Harris et al, 1976;Hummelgen et al, 1996;Yu et al, 2002;Siau et al, 2005;Crane et al, 2005;Kwon et al, 2011;Kwon and Marron, 2009). As a result, this study also computes the energy release rates for various situations to evaluate the joint strength of the hybrid composite.…”
Section: Description Of Analysis Modelsmentioning
confidence: 90%
See 1 more Smart Citation
“…Previous studies showed that calculation of energy release rates was very useful for predicting the interface joint strength of composites with known critical energy release rates (Kwon et al, 2008a, b;Faulkner and Kwon, 2011;Faulkner et al, 2009; Step/butted joint and step overlap joint Interface fracture of hybrid joint McGuire and Harris, 1974;Harris et al, 1976;Hummelgen et al, 1996;Yu et al, 2002;Siau et al, 2005;Crane et al, 2005;Kwon et al, 2011;Kwon and Marron, 2009). As a result, this study also computes the energy release rates for various situations to evaluate the joint strength of the hybrid composite.…”
Section: Description Of Analysis Modelsmentioning
confidence: 90%
“…The strength of scarf joints as well as an improvement of their joint strength using carbon nanotubes (Kwon et al, 2008b;Faulkner and Kwon, 2011;Faulkner et al, 2009) has been studied. The welding technique is a well-known joining technique for metals.…”
Section: Introductionmentioning
confidence: 99%